Association between gestation weight gain and postpartum poor sleep quality in postpartum women with weight retention - Ling Lim; Chu-Yi Chou; Tzu-Ling Chen; Chia-Sui Weng (Taiwanese Journal of Obstetrics & Gynecology)
Objective: Gestational weight gain (GWG) and sleep quality may cause postpartum weight retention (PPWR). Materials and methods: This was a cross-sectional study conducted from January to October 2022. A total of 282 postpartum women were recruited at 6 months postpartum, at which point postpartum weight was measured in our obstetrics and gynecology clinic. We classified participants into the two categories of excessive PPWR (≥5 kg) at 6 months postpartum or those without it. GWG was obtained from maternal health records. Weight gain during pregnancy was described as “insufficient” if below the Institute of Medicine recommendations (2009), “adequate” if within the recommended range, and “excessive” if above the recommendation. The Pittsburgh Sleep Quality Index was used to assess sleep during the previous 7 days. Results: Participants’ mean age was 36.1 ± 5.2 years. Poor sleep quality (OR: 10.9; 95 % CI: 4.04–29.49) was associated with excessive PPWR. Women with insufficient GWG (OR: 0.34; 95 % CI: 0.17–0.65) were less likely to reach substantial PPWR (OR: 0.51; 95 % CI: 0.26–0.98), while those with excessive GWG were more likely to do so (OR: 7.25; 95 % CI: 2.66–19.75). Conclusion: Health-care providers should recognize that encouraging appropriate GWG and the screening for sleep quality of postpartum women may reduce the incidence of substantial PPWR and thus reduce obesity rates in the early postpartum period.